Emotional Eating on Sedentary Workers: Is It Caused by Individual Characteristics, Exercise Habits, and Work Stress? - Irwansyah, Pindi Dwi; Arini, Shintia Yunita; Dwiyanti, Endang; Atmaka, Dominikus Raditya; Irwanto, Bian Shabri Putri; Jannah, Farahul (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction:Emotional eating is a person's response to stress or inadequate and ineffective stress coping and is shown by the behavior of eating more than needed and is associated with increased body weight. Emotional eating is caused by age, gender, exercise habits, and work stress. Based on the observations carried out at Kalla Group Office, employees tend to work in a monotonous and static manner that has the potential to increase the risk of emotional eating. The aim of this research is to determine the strength and weakness of the correlation between age, gender, exercise habits, and work stress with emotional eating in Kalla Head Office workers. Methods: This quantitative research was carried out through analytical observational design. The number of samples taken is 133 people using purposive sampling. In this case, the independent variables measured are age, gender, exercise habits, and work stress. Meanwhile, the dependent variable studied is the level of emotional eating using "The Dutch Eating Behavior Questionnaire of 13 items (DEBQ-13)". Data were further analyzed using Spearman correlation coefficient test (Spearman rho). Results: The research results show varied relationship with the independent variables including age (r = 0.052), gender (r = 0.251), exercise habits (r = -0.128), and stress (r = 0.048). Conclusion: Age is a variable that has the weakest relationship, while gender has the strongest relationship with emotional eating compared to the variables exercise habits and work stress.